EKSISTENSI MUSEUM RUMAH GADANG MANDE RUBIAH SEBAGAI IDENTITAS LOKAL MASYARAKAT DI KECAMATAN LUNANG KABUPATEN PESISIR SELATAN SUMATRA BARAT (1980-2023) - Alfarabi, Rofi; Isjoni; Surya Barkara, Refly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the existence of the Museum Rumah Gadang Mande Rubiah as a marker of local identity for the community in Lunang Subdistrict, Pesisir Selatan Regency, West Sumatra, from 1980 to 2023. The study has three main objectives: (1) to understand the existence of Mande Rubiah of the seventh generation and the Museum Rumah Gadang Mande Rubiah during the period 1980–2023; (2) to analyze the role of the museum’s development in shaping the cultural identity of the local community; and (3) to identify the supporting and inhibiting factors influencing the museum’s sustainability. This research employs a historical method consisting of four stages: Heuristics, Source Criticism, Interpretation, and Historiography. The findings reveal that the Museum Rumah Gadang Mande Rubiah represents the enduring strength of Minangkabau culture within Nagari Lunang. Originally guarded as a sacred and relatively concealed heritage site, the building has evolved into an educational and tourism center since its inauguration in 1980. Its unique and spiritually significant collections, including the Garuda bird egg and several ancestral graves, reinforce its status as an important cultural and religious site. The figure of Mande Rubiah VII continues to hold influence as a spiritual leader and customary decision-maker, despite lacking formal governmental authority. While the museum faces constraints such as limited funding and inadequate facilities, its development has been supported by strong community involvement and assistance from local government. As a cultural hub that drives customary, religious, and economic life, the museum demonstrates that ancestral heritage can coexist with modern development. In recognition of its significance, the museum has been registered as a Cultural Heritage Site under the Minister of Culture and Tourism Regulation Number PM.86/PW.007/MKP/2011.